A Bibliometric Analysis of Geographical Studies: A case study, Universitas Negeri Manado - Joy C. Kumaat,; Maxi Tendean,; A. A Tumengkol,; Xaverius E. Lobja,; Ruth S. Umbase, (Technium Social Sciences Journal, 2024)
This bibliometric study aims to analyse the research contributions of Universitas Negeri Manado (Unima) in the field of geography. The web application Biblioshiny and the bibliometric software VOSviewer were used for this purpose. The analysis uses visual representations of sources, authors and documents to illuminate the conceptual, intellectual and social structures within which these elements operate, thus providing insights that can inform future directions in geography research and identify avenues for improvement. The results show a significant increase in geography research publications in Unima, particularly noticeable from 2020 onwards. This suggests an increased interest and focus on the part of lecturers and researchers. In particular, the journals Geographia: Geography Education and Research and Episentrum Journal, it can be concluded from this analysis that they represent the two most important platforms for the publication of geography research at Unima. This is in line with the principle of Bradford's Law, which describes the uneven distribution of scholarship within a discipline. The contributions of leading researchers such as Xaverius Erick Lobja (XEL), Hermon Maurits Karwur (HMK) and Maxi Tendean (MT) are significant. This is evidenced by their extensive publications and their impact on the geography literature at Unima. The distribution pattern of authors and articles follows Lotka's law, where a small proportion of authors are highly productive, while most publish fewer articles. In addition, this study highlights the continuity of research over a long period of time, illustrating a deep commitment to the advancement of geographical knowledge at Unima. Keyword analysis and direct citation network construction were used to identify areas of focus in geography research. This study provides a comprehensive understanding of the evolution of geography research at Unima, providing a basis for strategic decision-making in shaping future research directions and fostering collaboration among researchers in the field.